Implementation of MAC Address Filtering as a Security System for Wireless Network Protection - Anugrah, Aditya Bayu (Faculty of Engineering, Universitas Tanjungpura, 2026)
Wireless networks are highly vulnerable to security threats, particularly unauthorized access. PT Borneo Cakrawala Media currently relies on the WPA2-PSK security mechanism, which has certain limitations. This study aims to implement MAC Address Filtering as an additional security mechanism for a wireless network. The research methodology includes the design, configuration, and testing of MAC Address Filtering using a Mikrotik RB750GR3 router and a Ruijie RG-720L access point. The tests were conducted on registered and unregistered device access, device addition and removal, false positive and false negative cases, MAC Address Spoofing handling, and network performance evaluation using Quality of Service (QoS) parameters based on the TIPHON standard. The results indicate that MAC Address Filtering is capable of accurately verifying registered devices and rejecting unauthorized devices, managing MAC Address addition and removal, and handling false positive and false negative cases with a 100% success rate without significantly degrading network performance. Furthermore, the MAC Address Spoofing tests demonstrate that the system can distinguish devices even when identical or similar MAC Addresses are used. It can be concluded that MAC Address Filtering is effective as an additional security mechanism for protecting wireless networks.